2019
DOI: 10.1073/pnas.1819541116
|View full text |Cite
|
Sign up to set email alerts
|

NRF2/ARE pathway negatively regulates BACE1 expression and ameliorates cognitive deficits in mouse Alzheimer’s models

Abstract: BACE1 is the rate-limiting enzyme for amyloid-β peptides (Aβ) generation, a key event in the pathogenesis of Alzheimer's disease (AD). By an unknown mechanism, levels of BACE1 and a BACE1 mRNA-stabilizing antisense RNA (BACE1-AS) are elevated in the brains of AD patients, implicating that dysregulation of BACE1 expression plays an important role in AD pathogenesis. We found that nuclear factor erythroid-derived 2-related factor 2 (NRF2/ NFE2L2) represses the expression of BACE1 and BACE1-AS through binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 53 publications
3
114
0
Order By: Relevance
“…e TF genes FSOL2, MESI2, NEF2L2, and PRDM2 have been reported to be associated with neurodegenerative diseases [60][61][62][63]. Moreover, the TF genes FSOL2, KLF11, and NEF2L2 play essential roles in the neurodegenerative diseases [64][65][66]. e analysis results in the current study suggested a potential cooperation manner of these TFs, which may provide evidence for further molecular mechanism research.…”
Section: Discussionsupporting
confidence: 54%
“…e TF genes FSOL2, MESI2, NEF2L2, and PRDM2 have been reported to be associated with neurodegenerative diseases [60][61][62][63]. Moreover, the TF genes FSOL2, KLF11, and NEF2L2 play essential roles in the neurodegenerative diseases [64][65][66]. e analysis results in the current study suggested a potential cooperation manner of these TFs, which may provide evidence for further molecular mechanism research.…”
Section: Discussionsupporting
confidence: 54%
“…This suggests CAW improves antioxidant signaling to combat the ever increasing oxidative stress mediated by the expanding Aβ pathology indicative of AD. Supplementation of NRF2 antioxidative mechanisms using the NRF2 activator sulforaphane improves cognitive function in 5XFAD and 3xTg-AD mouse models [102], providing supporting evidence of the cognitive benefit of added Nrf2 expression beyond that of the native 5XFAD pathology-driven increase.…”
Section: Discussionmentioning
confidence: 83%
“…Administration of sulforaphane ameliorated cerebral vasospasm and early brain injury through nuclear factor erythroid 2-related factor 2 (NRF2) signaling activation, which in turn induced antioxidant enzymes including heme oxygenase-1 (HO-1), gamma-glutamylcysteine synthase (GCS), and glutathione reductase and suppressed inflammatory responses [ 29 , 30 ]. In another study, Bahn et al revealed that sulforaphane attenuated both Aβ production and cognitive dysfunction through NRF2 activation in an AD mouse model [ 31 ].…”
Section: Resultsmentioning
confidence: 99%